The Analysis of the Broken Law Enforcement Chain of Regional Regulation No. 4/2019 Sanctions: A Study on Apparatus Constraints (Environmental Services) and Perception of Sanction Credibility in Payakumbuh City - Irvanda, Rico; Frinaldi, Aldri; Rembrandt, Rembrandt (Science and Environmental Journal for Postgraduate, 2025)
Payakumbuh City Regional Regulation No. 4 of 2019 was enacted to strengthen waste management sanctions, responding to the failure of the previous regulation. However, existing research (Syafer & Putera, 2024; Fadillah & Yuliarti, 2025) and internal government data (PTMP, 2023) confirm that the implementation of this Regulation continues to fail, public participation remains low, and sanctions are not being enforced. A research gap exists regarding why these sanctions fail to be executed. This study aims to analyze the juridical and sociological factors causing the broken law enforcement chain. Using a qualitative socio-legal approach, primary data were collected through in-depth interviews with the Environmental services (DLH) and community members, supported by document analysis. The findings reveal that the failure of sanction enforcement is systemic. The law enforcement chain is broken upstream (apparatus) due to two critical barriers within the Environmental Services: (1) A juridical barrier, namely the absence of a derivative City Regulation as the technical Standard Operating Procedure (SOP) for enforcement; and (2) A structural barrier, namely the shortage of supervisory personnel (only 1 Environmental Supervisor or PPLHD). The chain is broken downstream (public) because: (1) Sanctions lack credibility (the public has "never" witnessed fines or arrests); and (2) Apathy is entrenched by systemic failure (sorted waste is "mixed again" by officers). The strict Rp 50 Million sanction in the Regional Regulation (das sollen) has become a "paper tiger" (das sein) due to apparatus dysfunction and a lack of political will.